Perfil del consumidor del tabaco universitario - Alvarado Hernández, María Belén (2018)
Abstract: The objective of the research is to know the profile of the university tobacco consumers. And the analysis was made of 118 university students (men s: 70.30%). The type of research is descriptive, cross-sectional, the tobacco consumption selection variable was used, and the characteristics of the smoker will be described based on variables: (1) sociodemographic, (2) lifestyle and (3) psychosocial. An adhoc survey and nine standardized brief scales were applied in order to evaluate: tobacco use, anxiety, depression, stress, personality type A, loneliness, resilience, vital satisfaction, vital compromise and psychological inflexibility. The results show that university smokers have an age range between 18 and 28 years, mostly single men s, that smokers who are full-time have more hours off than the worker student, have not so healthy habits like a sedentary life (61%), bad diet (30%) and not restful sleep (45%), the smokers students has a high scores of median (50 percentile) in: personality type A (79%), stress (40%) and psychological inflexibility (25%)